The Correlation between Learners’ Motivation and Language Learning Strategies in EFL Context - Khairunnisa Dwinalida; Sholeh Setiaji (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2020)
This study investigated the correlation between students’ motivation and learning strategies of the students of a Polytechnic in Palembang. 31 students were selected as the sample to find out their motivation and their language learning strategies. Two sets of questionnaires, a set of motivational questionnaires which consist of 18 items, and strategies of language learning questionnaire, which consist of 14 items, were used in this study to see the correlation between the two variables. Correlation coefficient and descriptive analysis were used in analyzing data by using Pearson product moment. The result shows a positive correlation. To improve students’ motivation in learning the target language, teachers may provide learning materials, strategies, or teaching methods which are suitable for facilitating learners’ learning.